“Eccentric Existence”: David H Kelsey oor teosentriese menswaardigheid - Marais, Nadia (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
“Eccentric Existence”: David H Kelsey on theocentric human dignity Discourses on human dignity presuppose specific anthropologies, that respond to the question as to what a human being is. David Kelsey’s recently published theological anthropology, Eccentric Existence (2009), provides a particular view on what it means to be human and, in turn, what the dignity of human beings entails. This article distinguishes between five perspectives and two discourses on human dignity, and proceeds to analyse Kelsey’s understanding of human dignity with a possible contribution to these discourses and perspectives in mind. It is argued that Kelsey’s work could identify with both the discourse on justice and the discourse on flourishing, and that Kelsey’s insistence that the dignity of human beings lie outside of themselves safeguards that dignity in the “eccentric existence” of human beings.